Prevalence and molecular detection of infectious laryngotracheitis virus in chickens in selected areas of Bangladesh (Bangladesh Journal of Livestock Research, 2021)
Infectious laryngotracheitis (ILT) is a viral disease of poultry species caused by infectious laryngotracheitis virus (ILTV) that shows high morbidity and mortality. The present study was under taken for ILTV prevalence in broiler and layer chickens from four different geographical areas including Bogura, Gazipur, Chattogram and Dhaka districts during 2017 to 2018. Total 350 tracheal swabs were collected and were evaluated by real time RT-PCR (rRT-PCR). The overall 5.14% (18/350) ILTV prevalence was found that included 6.5% (13/200) in layer and 3.33% (5/150) in broiler chickens. The prevalence of ILTV was highest (10%) in layer chickens under age below 20 weeks and broiler chicks showed ILTV (1. 42%) infection when they were 7-14 days old. Winter season showed highest 6.6% prevalence whereas 5% and 3% prevalence were noticed at summer and rainy seasons, respectively.Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 113-117